P-BN46 Risk Factors for Anastomotic Stricture after Hepaticojejunostomy for Bile Duct Injury – A Systematic Review and Meta-Analysis. (16th December 2021) - Halle-Smith, James; Hall, Lewis; Mirza, Darius; Roberts, Keith
Abstract: Background: After major bile duct injury (BDI), hepaticojejunostomy (HJ) is usually required. This can lead to good long-term patency but anastomotic stricture unfortunately remains common cause of long-term morbidity after major BDI. Although risk factors for adverse outcomes of BDI repair are reasonably well understood, there is a need to assimilate high level evidence to establish risk factors specifically for development of anastomotic stricture after HJ for BDI. Methods: This was a systematic review of studies reporting rate of anastomotic stricture after HJ for BDI was performed according to PRISMA guidelines. Where possible, meta-analyses were then performed to establish risk factors for anastomotic stricture after HJ for BDI. Results: The meta-analyses performed included five factors with a total of 2, 155 patients from 17 studies. An increased rate of anastomotic stricture after HJ for BDI was shown amongst patients with concomitant vascular injury (OR 4.96; 95%CI 1.92-12.86; p = 0.001), post-repair bile leak (OR: 8.03; 95%CI 2.04-31.71; p = 0.003) and repair by non-specialist surgeon (OR 11.29; 95%CI 5.21-24.47; p < 0.0001). Level of injury according to Strasberg Grade did not significantly affect the rate of anastomotic stricture (OR: 0.97; 95%CI 0.45-2.10; p = 0.93). Due to heterogeneity of reporting it was not possible to perform meta-analysis for impact of timing of repair on anastomotic stricture rate. Conclusions: Repair by a non-specialist surgeon was the only modifiable risk factor revealed by this meta-analysis and systematic review, which demonstrates the importance of broad awareness of these data. That said, knowledge of these risk factors permits evidence-based risk stratification of follow-up as well as better informed consent and understanding of prognosis for patients who have experienced major BDI and require HJ.